Evaluation of Caspase-8 Level in Serum of Patients with Autoimmune Thyroid Disorders - Albadri, Mohammed; Nasser, Issam Jumaa; Ali A.A, Mahdi (Technium BioChemMed, 2024)
Autoimmune thyroid diseases (AITDs), including Graves’ disease and Hashimoto’s thyroiditis, are characterized by lymphocytic infiltration of the thyroid and the production of thyroid autoantibodies. While the etiology of AITDs is still not fully understood, a combination of genetic susceptibility and environmental triggers is believed to contribute to the breakdown in immune tolerance. This study aimed to evaluate the levels of thyroid hormones (T3, T4, TSH), Anti-thyroid peroxidase Abs (Anti-TPO Abs), Anti-Thyroglobulin Abs (Anti-TG(, and apoptosis marker (Caspase-8 ) in Iraqi patients with AITDs compared to healthy controls. A total of 1000 patients participated in the study 820 were excluded from the study because it was non-immune thyroid disease, and 180 subjects were recruited, including 60 Graves’ disease patients, 60 HT patients, and 60 healthy controls. Serum levels of T3, T4, TSH, Anti-TPO Abs and Anti-TG, caspase 8, and inhibin were measured. T3 and T4 levels were significantly decreased in Hashimoto’s thyroiditis patients and increased in Graves’ disease patients compared to controls. TSH was significantly elevated in Hashimoto’s thyroiditis and reduced in Graves’ disease patients. Caspase-8 was significantly higher in Hashimoto’s groups compared with the control group, and Significantly lower in Graves group compared with the control group. In conclusion, an altered balance in thyroid hormones, Anti-TPO Abs, Anti-TG, and apoptosis markers occurs in AITDs. Elevated caspase-8 suggests that increased apoptosis may contribute to thyroid damage in AITDs. Further research is needed to clarify the roles of these mediators in AITD pathogenesis.